Inculturation and ancestor veneration: The case of the Dagaaba Catholics. - Dapila, Fabian Naangmensuma. (University of Ottawa (Canada), 1995)
The tension between indigenous African cultures and religions on the one hand, and Christian Churches on the other, is a well known fact that has been addressed by all concerned but still not resolved. From the point of view of the Africans, the history of the Christian missions is filled with misunderstandings and a lack of sensitivity on the part of the Churches. The African Synod of Bishops held in Rome in April 1994, is only the latest example of the problems surrounding the Church's attitude towards African Christians. From a personal experience of the tension between indigenous African cultures and religions, the author analyses the situation of the Dagaaba Catholics as it exists and lays out the tools that can be used to come to a mutually acceptable solution. In the light of the ongoing modifications in the process of evangelization, the thesis explores the interaction between Catholic missionaries and the Dagaaba of Upper West Ghana from the beginning of the Christian mission to today. The area chosen for this study is ancestor veneration as it was and is practised by the Dagaaba. The discussion of the Dagaaba's beliefs and practices related to their ancestors showed, on the other hand, the centrality of the latter in the life of the Dagaaba, and on the other, important similarities with Christian attitudes towards the saints. Both Dagaaba ancestors and Christian saints are community heroes that were "sanctifed" by the group from which they hailed. They are models for the members of the respective communities. The images of the ancestors and saints are meant to establish a lasting memory of the heroes and make them ever-present. Both the Dagaaba sculptures and their ancestors and the statues of Christian saints are placed in locations where they are easily accessible, i.e., either the house or the church. As a result of the analysis the author confidently states that the integration of Dagaaba ancestor veneration with the Christian cult of the saints would be a vital step towards inculturation. If the Church were to allow the ancestors to play the role which in Christianity traditionally is played by the saints, Dagaaba Christians would become fully Christian and at the same time they would not feel that they have to abandon their African roots. The elements that play a vital part here are the naming of children after Dagaaba ancestors rather than European saints to whom the African have no relationship; the saying of prayers that include the ancestors; the celebration of the Eucharist in the consciousness that living and dead form the community of the faithful; and the performing of family rituals that involve past and present members. Together, clergy and lay persons must embark on the road towards inculturation. The process itself must be informed by thorough research into the genuine meaning of the beliefs and practices of Africans in view of the teachings of Christianity.
Keywords: Religion, General.